Digital economic literacy micro, small and medium enterprises (SMES) go online - Yosi Erlanitasari; Andre Rahmanto; Mahendra Wijaya (Universitas Negeri Yogyakarta, 2019)
Micro, Small and Medium Enterprises (SMEs) have a very vital role in the development and economic growth. In the history of the Indonesian nation's economy, SMEs as a support of the national economy. To make SMEs rise in class, a strategy is needed where one of them is the use of digital economic literacy. Development of digital-based SMEs needs to be done digital literacy so that when SMEs are able to utilize digital technology it will increase revenues by up to 80%. At present, the number of SMEs in Indonesia reaches 62,922,617 units of which the highest number is in the Micro Scale 62,106,900 business units (98.70%) with Small Business 757,090 units (1.20%), and Medium Enterprises 58,627 units (0 , 09%). This research was aimed at toanalyze the Go Online SMEs Movement program launched by the government from 2017 until now, even for the future this program will be launched. The research was conducted with a qualitative content analysis method in which primary data online portal research through the Google search engine. Whereas secondary data were obtained from government publications about the Go Online SMEs Movement program. Research shows that only 36% of SMEs in Indonesia is still struggling with conventional marketing. Meanwhile, 37% of SMEs only have basic online marketing capacity such as computer and broadband access. The remaining 18% of SMEs have medium online capacity because they can use websites and social media. Only 9% have digital marketing capacity that can be categorized as sophisticated. The study recommended the importance of the government conducting intensive socialization of the Go Online SMEs Movement. In fact, it must also be at the level of assistance for SMEs. SMEs must be the main players in the development of the digital economy in Indonesia. Collaboration between government and e-commerce is carried out continuously to make Indonesia the Digital Energy of Asia by 2020.Usaha Mikro, Kecil, dan Menengah (UMKM) memiliki peran yang sangat vital di dalam pembangunan dan pertumbuhan ekonomi. Dalam sejarah perekonomian bangsa Indonesia, UMKM sebagai penopang perekonomian nasional. Untuk menjadikan UMKM naik kelas, dibutuhkan strategi dimana salah satunya adalah penggunaan literasi digital ekonomi. Pengembangan UMKM berbasis digital perlu dilakukan literasi digital sehingga ketika UMKM mampu memanfaatkan teknologi digital akan meningkatkan penerimaan hingga 80%. Saat ini, jumlah UMKM di Indonesia mencapai 62.922.617 unit dimana dari jumlah tersebut terbanyak di Skala Mikro 62.106.900 unit usaha (98,70%) dengan Usaha Kecil 757.090 unit (1,20%), dan Usaha Menengah 58.627 unit (0,09%). Penelitian ini bertujuan untuk menganisis program Gerakan UMKM Go Online yang diluncurkan pemerintah sejak tahun 2017 sampai dengan sekarang, bahkan untuk masa yang akan datang program ini akan terus diluncurkan. Penelitian dilaksanakan dengan metode analisis isi kualitatif dimana data primer penelitian portal online melalui mesin pencari Google. Sedangkan data sekunder didapat dari publikasi pemerintah mengenai program Gerakan UMKM Go Online. Hasil peneitian menunjukkan hanya 36% UMKM di Indonesia masih berkutat dengan pemasaran konvensional. Sedangkan, 37% UMKM hanya memiliki kapasitas pemasaran online yang bersifat mendasar seperti akses komputer dan broadband. Sisanya, sebesar 18% UMKM memiliki kapasitas online menengah karena dapat menggunakan website dan medsos. Hanya 9% saja yang memiliki kapasitas pemasaran digital yang bisa dikategorikan canggih. Penelitian merekomendasikan pentingnya pemerintah melakukan sosialisasi secara intensif mengenai Gerakan UMKM Go Online. Bahkan, juga harus pada tataran pendampingan pada pelaku UMKM. UMKM harus menjadi pemain utama dari perkembangan ekonomi digital di Indonesia. Kolaborasi antara pemerintahan dan e-commerce dilakukan secara kontinyu untuk menjadikan Indonesia sebagai Digital Energy of Asia pada 2020.